Experiencing patient-experience surveys: a qualitative study of the accounts of GPs - Edwards, Adrian (Royal College of General Practitioners, 2011)
BACKGROUND: Despite policy and financial support for patient-experience surveys as feedback to modify clinical practice, their benefits and other effects remain unclear. AIM: This study aimed to examine the perspective of GPs who have engaged with such tools. METHOD: Qualitative semi-structured interviews with 30 GPs across south Wales, UK. The transcripts were analysed using a constant comparative method. RESULTS: The participants regarded patient feedback as highly important but felt that patient-experience surveys, as currently implemented, were hard to interpret. Reflecting on the doctor–patient interaction, participants perceived ambiguity about whether results were evaluating the individual or the GP practice, and whether they were directed towards the ‘practitioner-as-person’ or towards specific behaviours. A potential threat was posed in both interpretations, with the risk of damaging consequences for the practitioner and the nature of general practice. The tension between satisfying patients and performing good health care was a clearly voiced dilemma. Doctors did not feel confident in their ability to change in response to feedback, particularly outside a formal training environment. CONCLUSION: Patient evaluation is seen as a key part of multisource feedback for practising doctors. Clarity is needed about the purpose of evaluation – whether for organisational or personal ‘feedback’, and whether formative or summative – and there is a need for attention to the process, with trained facilitators, to ensure that doctors gain from structured reflection, and can minimise the potential negative effects of evaluation.